Social Media Communication in the Nepalese Universities: An Extended UTAUT for Faculty’s Academic Performance - Sah, Gunja Kumari; Shrestha, Sajeeb Kumar; Aryal, Bhoj Raj (Journal of Education Culture and Society, 2026)
Aim. The aim of the research is to examine the impact of social media communication on faculty’s use behavior and academic performance under the extended Unified Theory of Acceptance and Use of Technology model. It also examines the mediating effect of faculty use behaviour between social media communication and academic performance. Methods. The subjects of the study were considered 402 instructors, including 41 professors, 72 associate professors, and 289 lecturers from the Nepalese leading universities such as Tribhuvan University, Purbanchal University, Kathmandu University, Pokhara University, and Rajarshi Janak University, through the purposive sampling techniques. Positivist methods employed a deductive research approach for the collection of quantitative data with a structured questionnaire based on a seven-point Likert scale through stratified random sampling. All of the collected data was transferred into the AMOS software and analyzed by structural equation modelling for the depth information. Results. The result shows that social media communication significantly impacts faculty use behavior and academic performance, thereby supporting H1 and H2. The study also confirmed H3, showing that faculty use behaviour significantly mediates the relationship between social media communication and academic performance. Conclusions. The study adds unique value based on the extended UTAUT models that social media use behaviour is positively allied between social media communication and the academic performance of the university faculty. This study supports the faculty’s digital literacy initiatives by assisting in the development of social media integration policies with teaching and learning in the higher education institutions in Nepal to increase overall academic performance. This study also provides a foundation for Nepalese universities to realize the important role of social media in academic enhancement.